GERMINATION AND BIOCHEMICAL RESPONSES TO ALKALINITY STRESS IN TWO SESAME CULTIVARS - Mahdavi, Batool (Plant Breeding and Seed Science, 2016)
In this study, the effect of different alkaline concentrations (0, 10, 20, 30, 40, 50, 60 mM) on germination and biochemical characteristics of the two sesame (Sesamum indicum L.) cultivares (Dashtestan and GL-13) which are registered cultivars of Iran were investigated. The experiment was carried out in a completely randomized design with three replications. Results showed that , germination percentage, germination rate, shoot length and dry weight, root length and dry weight and K+ content decreased, whereas, malondialdehyde (MDA), proline, total soluble sugars and Na+ contents increased with increasing alkalinity stress. GL-13 cultivar had the least root and shoot length, proline and K+ content than Dashtestan.